Characterization of beneficial properties of plant growth-promoting rhizobacteria isolated from sweet potato rhizosphere - Yasmin, Farzana; Othman, Radziah; Sijam, Kamaruzaman; Saad, Mohd Said (Academic Journals, 2009)
Laboratory study was conducted to characterize the beneficial properties of plant growth-promoting rhizobacterial (PGPR) strains isolated from sweet potato rhizosphere. Fifteen rhizobacterial (PGPR) strains were screened for indole acetic acid (IAA) production with and without addition of the precursor L-tryptophan (L-TRP), phosphate-solubilizing activity, and nitrogen production, antagonistic activity against fungal pathogens, siderophore production and intrinsic antibiotic resistance. Results of the laboratory study showed that 15 rhizobacterial isolates were able to produce indole acetic acid (IAA). The concentration of IAA produced ranged from 3.84 - 13.33mg L-1. Addition of L-tryptophan (L-TRP) to the bacterial isolates increased the production of IAA ranging from 4.94 - 46.66 mg L-1. Six isolates (40%) were able to solubilize insoluble phosphate as evident by production of clear zone on calcium phosphate medium. All isolates were able to grow in N-free media indicating their abilities to produce nitrogen which ranged from 0.74 - 1.32 ppm. Three of the isolates produced fluorescent pigment on agar plate indicated their abilities to produce siderophores. Four isolates were able to inhibit the fungal pathogens Rhizoctonia sp.and Pythium sp. The intrinsic antibiotic test showed that all isolates were resistant against chloramphenicol (10 and 30 µg mL-1), Streptomycin (10 µg mL-1), Kanamycin (5 and 30 µg mL-1), Penicillin (10 µg mL-1) and tetracyclin (30 µg mL-1). The rhizobacterial isolates showed the several beneficial traits that could improve plant growth.